The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s10350-004-0710-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implications of hMLH1 and p53 Immunohistochemical Status in Right-Sided Colon Cancer

Abstract: Loss of hMLH1 expression is an independent predicator of improved survival in this series and perhaps the underlying cause of the observed survival difference associated with p53 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
12
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
(12 reference statements)
3
12
0
Order By: Relevance
“…A study by Gao et al demonstrated that tumor location was an independent protective survival indicator in mucinous adenocarcinoma (which is commoner in the proximal colon) -i.e. poorer outcome for rectal mucinous adenocarcinoma compared to right-sided mucinous adenocarcinoma[83].By exclusively considering the factors predicting survival in RCC, Smyth et al showed that loss of hMLH1 expression (leading to MSI positive tumor) was an independent predictor for improved survival, whereas aberrant p53 expression had no correlation to outcome[84].Meta-analysis by Guastadisegni et al has shown that MSI positive CRCs have better overalloutcome compared to microsatellite stable CRCs[85].Despite RCC being more likely to be MSI positive, the overall outcome and survival is still poor in RCC. To determine the independent factors contributing to poorer outcome in RCC, Phipps et al correlated MSI status with the oncological outcomes of over 3000 CRC patients according to the subsite.…”
mentioning
confidence: 98%
“…A study by Gao et al demonstrated that tumor location was an independent protective survival indicator in mucinous adenocarcinoma (which is commoner in the proximal colon) -i.e. poorer outcome for rectal mucinous adenocarcinoma compared to right-sided mucinous adenocarcinoma[83].By exclusively considering the factors predicting survival in RCC, Smyth et al showed that loss of hMLH1 expression (leading to MSI positive tumor) was an independent predictor for improved survival, whereas aberrant p53 expression had no correlation to outcome[84].Meta-analysis by Guastadisegni et al has shown that MSI positive CRCs have better overalloutcome compared to microsatellite stable CRCs[85].Despite RCC being more likely to be MSI positive, the overall outcome and survival is still poor in RCC. To determine the independent factors contributing to poorer outcome in RCC, Phipps et al correlated MSI status with the oncological outcomes of over 3000 CRC patients according to the subsite.…”
mentioning
confidence: 98%
“…The MMR defective tumours (Group 3) all demonstrated normal p53 expression, which is a recognized association of the mutator pathway [4,11]. This group of tumours demonstrated very few chromosomal aberrations with a median of 4 (range 0 Á/11) gross alterations, as described previously [12,13] and did not exhibit common deletions on 18q and 17p.…”
Section: Discussionmentioning
confidence: 70%
“…A trend for improved overall survival for patients with p53 mutations in distal colonic carcinomas analyzed by single-strand conformation polymorphism analysis (SSCP) was also shown (23). Other studies reported an unfavourable prognosis in patients with p53-positive carcinomas (12,13,(24)(25)(26)(27)(28), but only few multivariate analyses yielded a significant result in these studies (25). However, other authors did not found a correlation of p53 and prognosis (11,16,29,30).…”
Section: Discussionmentioning
confidence: 86%